Relationship of Corporate Social Responsibility and Positioning in clients of the Savings and Credit Cooperative Santa Catalina de Moquegua. Tacna agency. 2021 - Acosta Hinojosa, David (2021)
The financial entity Association of savings and credits Santa Catalina de Moquegua, specifically the subsidiary located in the city of Tacna, object of study, presents various problems, specifically the commitment to contribute part of its benefits to improve the environment, social, economic, regarding the achievement of its positioning in its clients.In this sense, we propose as a generic objective to be able to determine the relationship between the variables of corporate social responsibility and that of customer positioning.The methodology adopted was a non-experimental, cross-sectional, descriptive design, the technique was the survey and the instrument the questionnaire, using the Likert scale.In this way, the objectives outlined in the research were raised, concluding that there is indeed a high relationship between corporate social responsibility, social and economic responsibility with the positioning of clients; Corresponding to a moderate relationship between environmental responsibility and the customer positioning of the entity under study.